A case for caching file objects inside internetworks. - Danzig, Peter B. (Computer communication review.)
This paper presents evidence that several, judiciously placed file caches could reduce the volume of FTP traffic by 42%, and hence the volume of all NSFNET backbone traffic by 21%. In addition, if FTP client and server software automatically compressed data, this savings could increase to 27%. We believe that a hierarchical architecture of whole file caches, modeled after the existing name server's caching architecture, could become a valuable part of any internet.We derived these conclusions by performing trace driven simulations of various file caching architectures, cache sizes, and replacement policies. We collected the traces of file transfer traffic employed in our simulations on a network that connects the NSFNET backbone to a large, regional network. This particular regional network is responsible for about 5 to 7% of NSFNET traffic.While this paper's analysis and discussion focus on caching for FTP file transfer, the proposed caching architecture applies to caching objects from other internetwork services.